Innovation and the environmental Kuznets curve: the case of CO, NMVOCs and SOx in the Italian regions - Donatella Baiardi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
The paper explores the relationship between per capita income and three air pollutants, CO, NMVOCs and SOx, using a novel dataset based on the Italian regions. Given the central role of technological progress in long-term environmental problems, we empirically investigate the influence of innovation on the environmental Kuznets curve (EKC). The estimation results validate the EKC hypothesis for the three air pollutants considered. Furthermore, the influence of innovation on the inverted-U-shaped curve identified by the theoretical literature is empirically confirmed too.
Keywords: 330; Air pollutants; Environmental Kuznets Curve; Italian regions; Technological Progress